Quantifying the Sediment Transport Capacity in Eroding Rills Using a REE Tracing Method. (2nd June 2016) - Zhang, Qingwen; Lei, Tingwu; Huang, Xinjun
Abstract: Quantifying the sediment transport capacity is crucial for better understanding of water erosion process. The limit for quantifying soil erosion process is due to a lack of spatially distributed sediment data. The rare earth elements (REEs) are a group of elements with unique properties for the potential study of soil sediment transport capacity, due to its characteristics as being strongly bound to soil particles and not interfere with sediment detachment, and transportation processes. The objective of this study was to estimate the sediment transport capacity in eroding rills using the REE tracing method. Ten REE oxides (Ho2 O3, Tb4 O7, Eu2 O3, Yb2 O3, Dy2 O3, Sm2 O3, La2 O3, Tm2 O3, CeO2, and Nd2 O3 ) were used as tracers mixed with soil. A flume experiment combined with five slopes and four flow rates was conducted. Water flow rates of 2, 4, and 8 L min −1 (L min −1 ) were taken for the three steeper slopes in the experiment, and flow rates of 4, 8, and 12 L min −1 were taken for the two gentle slopes. Water flow was pumped to a tan and introduced to the inlet of a flume with 8‐m long and 0·1‐m wide, which were divided into ten equal segments, with each segment containing a tabbed REE‐soil mixture. The sediment load along different length rills was calculated from the REE concentrations in the eroded material and its background reference value. With an exponential rise to maximum equation between sediment loads with the downslope distance along eroding rills, we developed a method to quantify the sediment transport capacity. The results obtained by the REE tracing method confirmed that sediment transport capacity increased as a power function with flow rate and slope gradient, with a determination of coefficient ( R 2 ) of 0·93 ( p < 0·001). Sediment transport capacity was more dependent on the flow rate and less on the slope gradient with larger exponent for the flow rate. The results from this study showed that the REE method is helpful to estimate the sediment transport capacity in a concentrated flow on the sloping cropland, and to improve understanding the processes of water erosion. However, the feasibility of using the REE for quantifying sediment transport should be further investigated at the field scale on complex landscapes and under natural rainfall. Copyright © 2016 John Wiley & Sons, Ltd.